CONDUCT OF MAMMOGRAM EXAMINATION (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
A mammogram is a low-dose x-ray of breast tissue. Health care providers use mammograms or mammograms to look for early signs of breast cancer before symptoms appear. This is called a screening mammogram. Doctors will also use mammography to look for any abnormalities if you experience new symptoms, such as swelling, pain, discharge from the nipples, or changes in the skin of your nipples. It is necessary to be aware of this operation at the present time and to be aware of such an examination in time.